DAMPAK HUBUNGAN DIPLOMATIK AS - PERANCIS PASCA KASUS PENYADAPAN YANG DILAKUKAN OLEH AS TERHADAP PRESIDEN PERANCIS FRANCOIS HOLLANDE - Suwita Lora; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is a study of diplomacy which discusses about the impact of diplomatic relations after the wiretapping case conducted by the American against the French. Unauthorized wiretapping is an unlawful act which may interfere with a person's privacy. However, in the context of inter-state, tapping is actually a common practice, performed to determine the actualintentions of a country, especially with regard to the national interests. Besides, detailed information about the policy and its implementationneeds to be known in order to anticipate and prevent acts of surprise. Unauthorized wiretapping is a disgraceful act and a violation of ethics diplomacy, especially if applied to friendly countries as carried out by United States toward France.Herefore it is necessary to take bold steps yet precise and measurable actions. Crime or Cybercrime technology that refers to to cyberspace (cyberspace) and the criminal who uses a computer. Under these conditions, the relationship between the country much easier than before, a country may have a problem with other countries. One case that is happening now is a matter of American espionage conducted against the France. Actions taken by the American influence on diplomatic relations between the two countries, which has existed for a long time. Franch government’s take action to protect the state and its citizens in case of espionage.Keywords : Diplomacy, espionage, cybercrime, tapping